Considering agency in the education-migration nexus: a temporal analysis of structure-agency relations with student-migrants - Brotherhood, T (2020)
This thesis employs narrative research methods to provide empirical and theoretical insights into the role of individual agency in international students’ pre-, during- and post-study trajectories through the education-migration nexus in the UK and Japan. To engage with these issues, I assume a life-course perspective which posits “individuals’ ways of constructing their life-course through choices and actions” (Eteläpelto, Vähäsantanen, Hökkä, & Paloniemi, 2013, p. 59) as the locus of their agency. Drawing heavily on the “chordal triad” model of agency, the project places an empirical emphasis on capturing individuals’ “temporal-relational contexts” (Emirbayer and Mische, 1998), thereby accounting for the reciprocal influences of temporality and structure on international students’ agency throughout their trajectories. From such a perspective, the thesis seeks to answer the following central research question: